Analysis of Factors Related to Non-Auditory Effect Complaints in Rice Milling Workers in Kabila and Tilongkabila Districts, Bone Bolango Regency - Aulia Igirisa; Laksmyn Kadir; Putri Ayuningtias Mahdang (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Non-auditory effect complaints are the effects of noise that are not related to the auditory effect hearing function, including physiological, psychological, and communication disorders such as fatigue, stress, and concentration disorders, which are common in workers with high noise exposure, including in the rice milling industry. This study aims to determine the relationship between noise intensity, working period, and duration of exposure with non-auditory complaints in rice milling workers in Kabila and Tilongkabila Districts, Bone Bolango Regency. The type of research used in this study is Observational Analysis with a cross sectional research design. The population in this study used a total sampling technique. The number of samples in this study is as many as 70 workers in nine rice milling units in Kabila & Tilongkabila districts, Bone Bolango Regency. The data analysis method used is the Chi-square test. The results showed that there was a significant relationship between working time with (p-value = 0.006), while noise intensity was not significantly related to (p-value = 0.946) and length of exposure there was a significant relationship with (p-value = 0.000) with non-auditory effect complaints rice mill workers in Kabila & Tilongkabila district, Bone Bolango Regency. Workers are expected to increase awareness in maintaining occupational health by using ear protection regularly, making good use of rest time, and immediately reporting complaints such as fatigue, stress, and concentration disorders.